C–H and H–H activation at a di-titanium centre - Tsoureas, N; Green, J; Cloke, F (Royal Society of Chemistry, 2017)
The reaction of the bis(pentalene)dititanium complex Ti2(μ:η5,η5-Pn†)2 (Pn† = C8H4(1,4-SiiPr3)2) with the N-heterocyclic carbene 1,3,4,5-tetramethylimidazol-2-ylidene results in intramolecular C-H activation of one of the iPr methyl groups of a Pn† ligand and formation of a "tucked-in" bridging hydride complex. The "tuck-in" process is reversed by the addition of hydrogen, which yields a dihydride featuring terminal and bridging hydrides.